A history of infanticide in Britain, c. 1600 to the present - Kilday, Anne-Marie (Palgrave Macmillan, 2013)
List of figures -- Acknowledgements -- Investigating infanticide : an enduring phenomenon -- The archetype of infanticide in the early modern period -- Murderous mothers and the extended network of shame -- Monsters of inhumanity? : methods of infant disposal -- The pendulum of opinion : changing attitudes to infanticide -- Explaining infanticide : motives and causes -- The modern debate : getting away with murder? -- Bibliography